Wiki and threaded discussion for online collaborative activities: students' perceptions and use - Artino, Anthony R.; Ioannou, Andri (My University, 2009)
Investigating the affordances of different web technologies to support online collaborative learning (CL) has implications for future research and practice in online education. In addition to a threaded discussion (TD)-the predominant tool used to promote online collaboration today-we used a wiki with 15 graduate students in an online course. Students worked on two different group activities, first using the TD and then using the wiki. We investigated students' attitudes about their CL experience, as well as differences in their CL processes, after using each technology. Our findings suggest that there are clear benefits and limitations inherent to both technologies. The TD tool was preferred, yet students recognized the potential of the wiki to support collaboration. Practical implications and future directions are discussed, including the need for instructors to support and encourage discussion as a complement to wiki writing, scaffold and model the use of wikis, and create sufficiently complex group tasks to help make wiki use attractive and appropriate
Keywords: Online learning; Wiki; Threaded discussion; Collaboration; Collaborative learning; Computer-supported collaborative learning